Новые виды слизистых споровиков (Myxosporidia) от черноморской атерины - Каратаев, А.К.; Исков, М.П. (Вестник зоологии, 1984)
New Myxosporidia_Species from Black Sea Sand-Smelt, Atherina mochon pontica. Karatayev A. K., Iskov M. P.— Vestn. zoo, 1984, No. 1. Sphaeromyxa atherinea sp. n., vegetalive stage unknown; spores fusiform, with’ obtuse, slightly rounded ends; polar capsules pyriform, of equal size; sporal length 14.4-16.8 pm, width 3.6-4.0 um, polar capsules length 40-50 pm, diameter 24-3.0 wm, distance between polar capsules 4.05.0 im; cnidociliar length 18.0-35.0 um. Sinuolinea schulmani sp. n— vegetative stage unknown; spores small, rounded; polar capsules of almost equal size; sutural vallum strongly curved; largest spore diameler 8.0-9.0 um, diamelers perpendicular to it 76-85 um; polar capsules length 24-30 pm, diameter 2.0-2.4 pm; cnidociliar length 15.0-22.0 pm.